Image matching towards maturity - Skarlatos, Dimitrios (My University, 2000)
This paper deals with the least squares matching algorithm, focused on stereo pairs, without the use of epipolar geometry. The least squares matching algorithm although widely used has still some shortcomings, which in certain cases keep it away from commercial production. The shortcomings are the low reliability of the "successful" matches and the automation/adaptation of the algorithm, which has numerous parameters. These problems will be addressed in this paper by introducing a new algorithm for dynamic adaptation of the template size and two new algorithms to enhance accuracy and reliability. Discussion and examples will be presented along with proposals for further work, based on the combination of the three algorithms and the use of epipolar geometry.
Keywords: Algorithms; Automation; Image matching; Quality control; Surface reconstruction